Making waves: A cross-study analysis of young people's participation arenas in Scotland's schools. (February 2022) - Cross, Beth; Mannion, Greg; Shanks, Rachel
This article compares democratic participation research in Scottish schools over a 10-year period. The comparison reveals how 'organic' aspects of decision-making arise in arenas of school activity. We argue that research heretofore has focussed on pupil councils to the exclusion of more everyday embedded and embodied choices. Primary researchers in the studies revisited data, drawing on their respective theoretical frameworks, to consider how new materialist perspectives offer ways to attend differently to the recursive, relational dynamics of participation.